Activation of GSK3 Prevents Termination of TNF-Induced Signaling - Welz B; Bikker R; Hoffmeister L; Diekmann M; Christmann M; Brand K; Huber R (Dove Medical Press, 2021)
Bastian Welz,* Rolf Bikker,* Leonie Hoffmeister, Mareike Diekmann, Martin Christmann, Korbinian Brand,* René Huber* Institute of Clinical Chemistry, Hannover Medical School, Hannover, 30625, Germany*These authors contributed equally to this workCorrespondence: Korbinian BrandInstitute of Clinical Chemistry, Hannover Medical School, Carl-Neuberg Str. 1, Hannover, 30625, GermanyTel +49 511 532 6614Fax +49 511 532 8614Email brand.korbinian@mh-hannover.deBackground: Termination of TNF-induced signaling plays a key role in the resolution of inflammation with dysregulations leading to severe pathophysiological conditions (sepsis, chronic inflammatory disease, cancer). Since a recent phospho-proteome analysis in human monocytes suggested GSK3 as a relevant kinase during signal termination, we aimed at further elucidating its role in this context.Materials and Methods: For the analyses, THP-1 monocytic cells and primary human monocytes were used. Staurosporine (Stauro) was applied to activate GSK3 by inhibiting kinases that mediate inhibitory GSK3α/β-Ser21/9 phosphorylation (eg, PKC). For GSK3 inhibition, Kenpaulone (Ken) was used. GSK3- and PKC-siRNAs were applied for knockdown experiments. Protein expression and phosphorylation were assessed by Western blot or ELISA and mRNA expression by qPCR. NF-κB activation was addressed using reporter gene assays.Results: Constitutive GSK3β and PKCβ expression and GSK3α/β-Ser21/9 and PKCα/βII-Thr638/641 phosphorylation were not altered during TNF long-term incubation. Stauro-induced GSK3 activation (demonstrated by Bcl3 reduction) prevented termination of TNF-induced signaling as reflected by strongly elevated IL-8 expression (used as an indicator) following TNF long-term incubation. A similar increase was observed in TNF short-term-exposed cells, and this effect was inhibited by Ken. PKCα/β-knockdown modestly increased, whereas GSK3α/β-knockdown inhibited TNF-induced IL-8 expression. TNF-dependent activation of two NF-κB-dependent indicator plasmids was enhanced by Stauro, demonstrating transcriptional effects. A TNF-induced increase in p65-Ser536 phosphorylation was further enhanced by Stauro, whereas IκBα proteolysis and IKKα/β-Ser176/180 phosphorylation were not affected. Moreover, PKCβ-knockdown reduced levels of Bcl3. A20 and IκBα mRNA, both coding for signaling inhibitors, were dramatically less affected under our conditions when compared to IL-8, suggesting differential transcriptional effects.Conclusion: Our results suggest that GSK3 activation is involved in preventing the termination of TNF-induced signaling. Our data demonstrate that activation of GSK3 – either pathophysiologically or pharmacologically induced – may destroy the finely balanced condition necessary for the termination of inflammation-associated signaling.Keywords: TNF, GSK3, PKC, staurosporine, IL-8, NF-κB, termination of TNF-induced signaling, termination of inflammation